Development of a portable solar-powered traffic light control system for a remote single lane bridge - Azau M.A.M.; Jaafar S.; Saedon M.Y. (Asian Research Publishing Network, 2023)
The uncertainties of terrain in some rural area in Malaysia make the building of a bridge a real challenge. When the construction of a bridge is built over railways, space is a matter of concern. This paper proposed a stand-alone traffic light solution for the drivers and motorist in Kampung Batang Benar, Negeri Sembilan who need to cross the railways via a single lane bridge. The single lane bridge can only accommodate one vehicle at one time and motorists have to wait for their turn to cross to the other end. Having a single lane bridge with no traffic light to control the traffic definitely contributes to congestion. On a peak hour, cars and motorcycles start to queue and there is no ruling on which end should go first. It will be a costly and not reliable approach to station traffic controller personnel at such a place. This project develops a portable stand-alone traffic light which uses Arduino microcontroller and Xbee wireless communication system. Since the system is using a wireless communication and portable, its usage can be extended to any remote road in the rural area to assist the traffic flow. The system is also equipped with solar photovoltaic and a battery bank to ensure the operation is continuous even during the night. The implementation of this system is perceived to put the traffic under control with minimal assistance from human operator.